Osseous dysplasia: An aggressive swelling at an uncommon site. Issue 3 (May 2016) - Singh, Pratyush; Shergil, Ankur; Solomon, Monica; Carnelio, Sunitha
Abstract: Osseous dysplasia (OD) are idiopathic processes located in the periapical region of the tooth bearing areas jaws areas characterized by a replacement of normal bone by fibrous tissue and metaplastic bone. These are categorized into four types on basis of the clinical and radiographic features: periapical, focal and florid and familial gigantiform cementoma. Periapical OD (PerOD) is the most common, followed by Focal OD (FocOD) and Florid OD (FloOD). Per OD is confined to the anterior aspect of the jaw while Foc OD and Flo OD are related to posterior mandibular region. Most of these have a benign course and are asymtomatic, but can be aggressive with a rapid increase in size and other symptoms. We report a case of OD of posterior maxilla, an uncommon site, in a 46-year-old female who presented with pain and increase in the size of the swelling and was adequately treated.